Effect of linoleic acid supplementation on triglyceride content and gene expression in milk fat synthesis in two- and three-dimensional cultured bovine mammary epithelial cells. Issue 3 (3rd July 2018) - Li, Dabiao; Xing, Yuanyuan; Li, Honglei; Wang, Weiyun; Hou, Xianzhi; Gao, Min
Abstract: In this study, the effect of 0, 40, and 80 μmol/L of LA on triglyceride (TG) content was evaluated, as well as the mRNA expression of genes involved in milk fat synthesis in bovine mammary epithelial cells (BMECs) which were cultured in two-dimensional (2D) and three-dimensional (3D) models. TG content was measured with a TG determination kit, and the expression of genes was measured with real-time quantitative polymerase chain reactions (RT-qPCR). Adding 80 μmol/L of LA significantly increased intracellular TG content in both 2D and 3D cultured BMECs ( p  < .05). The mRNA expression of diacylglycerol acyltransferase 2 ( DGAT2 ) and peroxisome proliferator-activated receptor-γ ( PPARG ) increased with the addition of 80 and 40 μmol/L of LA, respectively ( p  < .05), whereas the expression of PPARG was downregulated in the 2D model ( p  < .05). Adding LA significantly reduced the expression of sterol regulatory element-binding transcription factor 1 ( SREBF1 ), acetyl-CoA carboxylase ( ACC ), fatty acid synthase ( FASN ), stearoyl-CoA desaturase ( SCD ), and fatty acid-binding protein 3 ( FABP3 ) compared to the control group ( p  < .05). Altogether, TG content in BMECs and expression of genes involved in milk fat synthesis were significantly higher with addition of LA under 3D BMECs culture model than those of 2D ( p  < .05), and 40 and 80 µmol/L of LA inhibited the de novo synthesis of fatty acids and promoted the expression of DGAT2 and accumulation of TG. The mRNA expression of PPARG in 3D model was increased by addition of 40 μmol/L LA, whereas it was downregulated in 2D model.